MODERNIZATION OF THE HEAT TEMPERATURE CONTROL SYSTEM IN THE TECHNOLOGICAL CHANNELS OF THE ATOMIC REACT - A. L. Lyashenko (Современная наука и инновации)
He article describes the control system of technological parameters in the reactor core of the RBMK-1000. A scheme for the design of the graphite core of the reactor core is described. The technique of modeling objects with distributed parameters is considered. A technique for mathematical modeling of heat propagation in a cell of a technological channel is developed. The developed technique will allow to diagnose the physical condition of the power unit.